2007
DOI: 10.1063/1.2717892
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional dusty plasma crystal as an electrostatic wiggler for free-electron laser

Abstract: The ability of a dusty plasma crystal to induce transverse motion to a relativistic electron, as a microstructure wiggler field in a free-electron laser ͑FEL͒, is presented. A dusty crystal wiggler with micrometer size can decrease FEL wavelength several orders of magnitudes. A relativistic electron dynamic through a two-dimensional monolayer hexagonal dusty crystal is analyzed. In addition to the usual transverse wiggling motion, second-harmonic amplitude is induced to the axial velocity. These conditions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…which is performed by a coaxial structure: the outside surface of the inner rod is smooth and grounded; the inside surface of the outer conductor is connected to a negative voltage and corrugated with sinusoidal ripples. * sczhang@home.swjtu.edu.cn Recently, a two-dimensional dusty plasma crystal [12] or a planar electrostatic system [13] was proposed as an electrostatic wiggler for FEL. Excluding the space-charge wave in the aforementioned three-wave interaction mechanism, it is found that a planar electrostatic wiggler [13] may be favorable for a mildly relativistic electron beam to generate terahertz waves by extracting the kinetic energy of the electrons [14].…”
Section: Fig 1 Schematic Diagram Of a Coaxial Electrostatic Wigglermentioning
confidence: 99%
See 1 more Smart Citation
“…which is performed by a coaxial structure: the outside surface of the inner rod is smooth and grounded; the inside surface of the outer conductor is connected to a negative voltage and corrugated with sinusoidal ripples. * sczhang@home.swjtu.edu.cn Recently, a two-dimensional dusty plasma crystal [12] or a planar electrostatic system [13] was proposed as an electrostatic wiggler for FEL. Excluding the space-charge wave in the aforementioned three-wave interaction mechanism, it is found that a planar electrostatic wiggler [13] may be favorable for a mildly relativistic electron beam to generate terahertz waves by extracting the kinetic energy of the electrons [14].…”
Section: Fig 1 Schematic Diagram Of a Coaxial Electrostatic Wigglermentioning
confidence: 99%
“…Superposing the solutions for both ¼ 0 and for ¼ q 2 > 0, Eqs. (12) and (22), we obtain the general solution of Eq. (2):…”
Section: Derivation Of General Solutionmentioning
confidence: 99%
“…Microstructure electrostatic wigglers is a new possible application of complex plasma crystals. It is suggested by Mirzanejhad and Bahadory [12]. Electrostatic wigglers can transfer energy to relativistic electron beam in FELs.…”
Section: Introductionmentioning
confidence: 99%
“…In the microstructure electrostatic wiggler, charge and consequentially potential and electric field of individual grains are important [12]. Average grain charge has been already reported, but there are no experimental measurements of individual grains charge.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the ability of dusty plasma crystals to create transverse motion of the relativistic electrons and to use as an electrostatic wiggler has been proposed. [5][6][7] Many theoretical investigations for a FEL with longitudinal electrostatic wiggler have been done. A study of Bekefi,8 in such a FEL with completely filled waveguide and infinite axial magnetic field, showed that this system can be useful to produce millimeter wavelength radiation.…”
Section: Introductionmentioning
confidence: 99%